Landslide Susceptibility Analysis Of The Erzincan Basin Using The Frequency Ratio Method - Uysal, Ahmet; Sunkar, Murat; Gürgöze, Serkan (Ankara University, 2026)
In this study, landslide susceptibility analysis was conducted for the Erzincan Basin located in the Upper Euphrates Section of the Eastern Anatolia Region. In the mountainous areas surrounding the basin, especially in the north, the risk of landslides is very high. Due to the fact that the mountainous areas are cut by faults, large-scale landslides have occurred on the slopes bordering the basin, most of which were triggered by earthquakes. These landslides can cause disasters by affecting transport routes and settlements. Sensitivity analyses are used to identify risk areas and take measures against disasters. For this purpose, analyses were carried out with the Frequency Ratio (FR) method with satellite imagery and Geographic Information Systems (GIS) software such as ArcMAP 10.4.1, ArcGIS Pro and a landslide susceptibility map of the basin was prepared. In this study, 12 parameters were used that are effective in the formation of landslides including slope, aspect, elevation, lithology, slope curvature, rainfall, distance to fault lines, distance to roads, distance to streams, land cover, soil, and Topographic Wetness Index (TWI). The FR values of these parameters were calculated and a landslide susceptibility map was produced by correlating these values with the landslides. According to the analysis results, 22.21% of the basin has very low sensitivity values, 30.22% has low sensitivity values, 43.97% has medium sensitivity values, 1.15% has high sensitivity values, and 2.45% has very high sensitivity values. Although the rate of areas with high and very high sensitivity is low throughout the basin, they cover a large area. According to the ROC Curve method, the calculated value of 0.81 indicate a high accuracy rate. © 2026, Ankara University. All rights reserved.
Erzincan Havzası’nın Frekans Oranı Yöntemine Göre Heyelan Duyarlılık Analizi
Keywords: Erzincan Basin; Frequency Ratio; Landslide Susceptibility Analysis; Natural Disaster